A importância da reciclagem e da coleta seletiva no contexto escolar, como contribuição na preservação do meio ambiente - Cardoso, Marciele dos Santos (Brasil, 2022)
Currently, the world has many problems related to pollution, one of them is the inadequate waste disposal, which ends up generating many problems for society, the environment, the fauna and the flora. For this reason, a reflection on the strategies used in classroom science teaching with regard to materials recycling is important, as today’s students will be the future of society and need to have a more environmental awareness so that take better care of the planet. Thus, this research had as its main objective to sensitize the students of the 6th grade about the waste produced by them, and to transform this waste into products such as toys and handicrafts. It was held at the Paula Ângela Francinetti State school, located in the south of Manaus – AM. Therefore, a methodology of this study was based on the theoretical exposition classes, involving issues inherent to the theme, then groups were created for making crafts and toys, from recyclable materials that were previously wasted in everyday life for use presented in the workshop. Initially, we applied a previous questionnaire about student’s knowledge about basic questions: what is garbage? What is selective collection? Later it took place in a laboratory in which students exposed their confections and commented on the respect of which materials were reused and how important this process was. At the end of the workshop, a questionnaire is applied with questions on all subjects covered in the lectures, also conducted a qualitative assessment in which you should analyze the ideas of students after the teaching learning process on the developed theme. This study indicated results that reaffirm the effectiveness of theoretical and practical exposition in the process of teaching and learning in science, highlighting the form, which is the importance of using practices in science education.